2021
DOI: 10.5815/ijcnis.2021.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multicast and Unicast Routing Protocols Performance for Group Communication with QoS Constraints in 802.11 Mobile Ad-hoc Networks

Abstract: In Mobile Ad-hoc Network (MANET), portable devices like smartphones, or laptop PC can join together to make provisional networks without any infrastructure The objective of multicast or unicast protocols is to ensure an efficient route formation and flow control mechanism which is a very challenging issue for many group computing services in MANETs. MANETs can support several real-time applications like emergency rescue, and disaster relief operations which require minimum Quality of Service (QoS) to handle hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…In terms of building UAV group collaborative network by using blockchain technology, the data blocks are combined into specific data structures in a chain manner in chronological order, and the tamper proof and forgeable decentralized shared ledger guaranteed by cryptography can safely store simple, sequential and verifiable data in the system 10 . Debnath and others found that blockchain system mainly solves the Byzantine general problem in the interaction process of distributed system, that is, how distributed nodes reach consensus and establish mutual trust in the absence of trusted central nodes 11 . Chettri and others believe that based on the consensus mechanism of blockchain, combining blockchain with UAV network to form a group network can provide a more secure, flexible and efficient information sharing and decision‐making mechanism for UAV collaborative control 12 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of building UAV group collaborative network by using blockchain technology, the data blocks are combined into specific data structures in a chain manner in chronological order, and the tamper proof and forgeable decentralized shared ledger guaranteed by cryptography can safely store simple, sequential and verifiable data in the system 10 . Debnath and others found that blockchain system mainly solves the Byzantine general problem in the interaction process of distributed system, that is, how distributed nodes reach consensus and establish mutual trust in the absence of trusted central nodes 11 . Chettri and others believe that based on the consensus mechanism of blockchain, combining blockchain with UAV network to form a group network can provide a more secure, flexible and efficient information sharing and decision‐making mechanism for UAV collaborative control 12 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…10 Debnath and others found that blockchain system mainly solves the Byzantine general problem in the interaction process of distributed system, that is, how distributed nodes reach consensus and establish mutual trust in the absence of trusted central nodes. 11 Chettri and others believe that based on the consensus mechanism of blockchain, combining blockchain with UAV network to form a group network can provide a more secure, flexible and efficient information sharing and decision-making mechanism for UAV collaborative control. 12 In China, Tsinghua University, Peking University, University of Electronic Science and technology, Beijing University of Posts and telecommunications, University of national defense science and technology, Xi'an Jiaotong University, Air Force Engineering University and Northwest University of technology have done relevant research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It generates the routing path with the number of intermediate nodes from the source to the destination nodes. Typically, routing protocols are either unicast or multicast which depends on the method used for data transmission [3]. Unicast transmission can deliver the data packets to only one destination node whereas multicast transmission can deliver the data packets simultaneously to the group of destination nodes [4].…”
Section: Introductionmentioning
confidence: 99%